Cinema at the End of Empire : A Politics of Transition in Britain and India - Jaikumar, Priya, 1967- (Book collections on Project MUSE., 2006)
History of the relationship between government regulation of the film industry in the UK and the the developing film industry in India between the 1920s and 1940s.